(untitled) (Bangladesh Journal of Agricultural Research, 2015)
The study was carried out in the research field and laboratory of the Department of Horticulture, Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU), Gazipur-1706 during October 2011 to April 2012 to determine optimum level of nitrogen and spacing for improving the nutritional quality of broccoli. There were 15 treatments in the experiment comprising five levels of N viz., 0, 80, 120,160, and 200 kg/ha and three plant spacings viz., 60cm x 60cm, 60cm × 45cm, and 60cm × 30cm. The results revealed that the highest ascorbic acid content (50.38 mg/100g) was obtained from S60X30N0 and the highest b-carotene content (50.67 IU/100g) was found in S60X60N0. Maximum Ca (0.556%) was found in S60X60N0 whereas maximum Fe (159.002 ppm) was in S60X60N200. The maximum P content (0.081%) was observed in S60X60N160 and maximum K content (0.854%) was found in S60X45N160. DOI: http://dx.doi.org/10.3329/bjar.v39i3.21992 Bangladesh J. Agril. Res. 39(3): 491-504, September 2014